Telaah Metode Pengujian Aktivitas Antioksidan pada Teh Hijau (Camellia sinensis (L.) Kuntze) - Risma Aryanti; Farid Perdana; Raden Aldizal Mahendra Rizkio Syamsudin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Green tea (Camellia sinensis (L.) Kuntze) is a trendy herbal drink with many benefits, one as an antioxidant. Catechin from the flavonoid class (polyphenols) in green tea is responsible for determining tea's antioxidant properties. Much research measures antioxidant activity in green tea, so it has to compare the antioxidant activity testing method to see which one method is better based on their mechanism in action. The antioxidant activity testing methods were used are DPPH (1,1-diphenyl-2-picrylhydrazyl), ABTS, FRAP (Ferric Reducing Antioxidant Power), CUPRAC (Cupric Reducing Antioxidant Capacity), and ORAC (Oxygen Radical Absorbance Capacity). The results showed that the highest antioxidant activity in green tea was obtained using the ABTS method expressed in Trolox Equivalent, equal to 3210 μmol TE/g with a total phenol of 240.73 mg GAE/g.